2017
DOI: 10.1155/2017/5495808
|View full text |Cite
|
Sign up to set email alerts
|

From Bad to Worse: Paraganglioma Diagnosis during Induction of Labor for Coexisting Preeclampsia

Abstract: Pheochromocytomas and extra-adrenal paragangliomas are catecholamine-secreting tumors that rarely occur in pregnancy. The diagnosis of these tumors in pregnancy can be challenging given that many of the signs and symptoms are commonly attributed to preeclampsia or other more common diagnoses. Early diagnosis and appropriate management are essential in optimizing maternal and fetal outcomes. We report a rare case of a catecholamine-secreting tumor in which diagnosis occurring at the time labor was being induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…314 Maternal and fetal mortality were as high as 28% and 27%, respectively, when there was a delay in diagnosis and treatment. 314,315 Only a few studies have reported that patients with pheochromocytoma develop superimposed preeclampsia; 294,295 therefore, the existence of an association is not yet clear. 314…”
Section: Expert Reviewmentioning
confidence: 99%
“…314 Maternal and fetal mortality were as high as 28% and 27%, respectively, when there was a delay in diagnosis and treatment. 314,315 Only a few studies have reported that patients with pheochromocytoma develop superimposed preeclampsia; 294,295 therefore, the existence of an association is not yet clear. 314…”
Section: Expert Reviewmentioning
confidence: 99%
“…There is lack of consensus as to the preferred route of delivery in pregnant women as of date possibly due to the rarity of the disease and paucity of evidence, wherein patients are managed on a case-to-case basis. In this case, the maternal and fetal outcomes were unaffected even though the patient was harboring the tumor, but this cannot be generalized 10,12 . Antenatal diagnosis of pheochromocytoma can have a positive impact on both maternal and fetal outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Antenatal diagnosis of pheochromocytoma can have a positive impact on both maternal and fetal outcomes. If diagnosed antenatally, a fall in mortality rates from 29% to 0%, and also from 29% to 12% have been reported for mother and fetus, respectively 10 , 12 . Fortunately, our patient had an uneventful perioperative and postnatal period until pheochromocytoma became evident.…”
Section: Discussionmentioning
confidence: 99%
“…12 Women with both pre-existing and newly diagnosed secretory paragangliomas require timely multi-disciplinary care through all phases of care from pre-pregnancy to the post-partum period. 6,19,20…”
Section: Introductionmentioning
confidence: 99%
“…16 In pregnancy, some of these clinical features may be attributed to physiological changes of pregnancy, pre-eclampsia or other pregnancy-related causes of hypertension. [17][18][19] Therefore, clinicians must maintain a high level of clinical suspicion in the case of pregnant women with severe hypertension or other features of catecholamine excess. 12 Women with both pre-existing and newly diagnosed secretory paragangliomas require timely multi-disciplinary care through all phases of care from pre-pregnancy to the post-partum period.…”
Section: Introductionmentioning
confidence: 99%